Morphometric and anatomical characters of fruits and seeds of a population of Prosopis laevigata (Fabaceae) in Lagos de Moreno, Jalisco, Mexico - García Azpeitia, Lilia; Labrada-Delgado, Gladis Judith; Montalvo-González, Efigenia; Loza-Cornejo, Sofía (Instituto de Ecología, A.C., 2022)
Background and Aims: Prosopis laevigata, a widely distributed species in Mexico, is considered a resource with ecological and socioeconomic importance. Although its seeds and fruits have nutritional value, research on its morphological and anatomical variation is scarce. This study is the first to address the morpho-anatomy and histochemistry of the fruit and seed of P. laevigata and aims to contribute to the knowledge of its biology, as well as provide the basis for other research with an ecophysiological approach of this and other species of the genus. Methods: Fruit and seed samples were collected from Prosopis laevigata trees in a locality of Lagos de Moreno, Jalisco, Mexico, to analyze their morphometric, anatomic, and histochemical characters. Additionally, its micro elemental composition was studied by scanning electron microscopy (SEM) coupled to energy-dispersive X-ray spectroscopy (EDS). ANOVA and correlation analyzes were applied to determine intrapopulation variability and association between morphometric variables. Key results: The highest coefficient of variation (47.7%) was for the number of seeds per fruit. The ANOVA showed significant statistical differences for the variables seed length (F=7.51, p<0.0001) and seed width (F=8.75, p<0.0001); the highest correlation (0.937) was for fruit width-seed width. The fruits have an epicarp, mesocarp with calcium oxalate crystals and a leathery endocarp. The seeds present a pleurogram, subapical micropyle, and a thick seed coat with an epidermis of macrosclereids, and osteosclereids in the hypodermis. Cotyledons contain protein bodies and starchy endosperm. The testa and the embryo present macroelements (S, K, Mg) and microelements (Al, Si, Cu). Conclusions: The morphological and anatomical characteristics and histochemical structure of fruits and seeds of the P. laevigata were similar to other Prosopis. The palisade epidermis, hypodermis with osteosclereids in the seed coat, stomata and prismatic crystals in the pods could represent important ecophysiological characters.